2008
DOI: 10.1007/s10664-008-9065-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of agile practices on communication in software development

Abstract: Agile software development practices such as eXtreme Programming (XP) and SCRUM have increasingly been adopted to respond to the challenges of volatile business environments, where the markets and technologies evolve rapidly and present the unexpected. In spite of the encouraging results so far, little is known about how agile practices affect communication. This article presents the results from a study which examined the impact of XP and SCRUM practices on communication within software development teams and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(200 citation statements)
references
References 50 publications
5
186
0
9
Order By: Relevance
“…Large scale projects therefore require a more disciplined approach to software development (Ambler, 2008). There is also evidence that large scale projects may exacerbate communication problems (Pikkarainen et al, 2008).…”
Section: Enterprise Agilementioning
confidence: 99%
“…Large scale projects therefore require a more disciplined approach to software development (Ambler, 2008). There is also evidence that large scale projects may exacerbate communication problems (Pikkarainen et al, 2008).…”
Section: Enterprise Agilementioning
confidence: 99%
“…Scrum recommends that the DSM should not be used for discussing solutions to obstacles raised. However, empirical studies have found that spending time in the short meeting on discussing and solving problems is valuable [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Assim, a adoção de metodologias ágeis pode impedir a criação e manutenção de conhecimento organizacional (Pikkarainen, 2008;Santos et al, 2015Santos et al, , 2015, o que pode impactar na capacidade absortiva e desempenho da organização (Naim & Lenka, 2016;Paulsen & Hjertø, 2014;Van Wijk et al, 2008).…”
Section: Equipas áGeis Como Contexto Para Orientação Pra Objetivos Punclassified